System Approach in Law Cognition (the experience of Chair of Constitutional, Administrative and Finance Law of the Faculty of Law of Yuri Fedkovich Chernivtsi National University) - Patsurkivskyy, Petro (РУСЕНСКИ УНИВЕРСИТЕТ „Ангел Кънчев“, 2011)
Law, including positive, is an attributive system phenomenon in its origin. Its es sence was understood and demonstrated on the example of its juridical constructions by ancient- roman lawyers. Nevertheless, as the analysis of the world jurisprudence devel opment proves, its history is so far formed in such a way, that system investigations of Law as the phenomenon of an objective reality, especially its system characteristics, were per formed from time to time and only by some scientists. Obviously, that is why no one home or foreign scientific school of Finance Law exists able to elaborate the experience of apply ing the system approach to finance- legal reality so necessary for modern science of Fi nance Law. In this situation any rational way out but applying the methodological experi ence of system investigations of other sciences doesn’t exist.
Keywords: Tax Law; Finance Law